2022
DOI: 10.1111/cpf.12741
|View full text |Cite
|
Sign up to set email alerts
|

The impact of isometric handgrip exercise and training on health‐related factors: A review

Abstract: Isometric handgrip exercise has been suggested to promote some health‐related factors (e.g., lowering blood pressure). However, there is a need to evaluate whether this type of exercise can be included as an option to elicit these health‐related outcomes. The purpose of the article was to systematically review the acute and chronic effects of isometric handgrip exercise on resting blood pressure, pain sensation, cognitive function and blood lipids and lipoproteins. A systematic review was performed according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 118 publications
(274 reference statements)
0
3
0
Order By: Relevance
“…Grip strength correlates with mortality [ 90 92 ] and ability to perform activities of daily living [ 93 96 ]. Moreover, one review concluded that isometric hand grip exercise, which is often minimal in its prescription, reduces resting systolic blood pressure and induces hypoalgesia [ 97 ]. Also, the ability to perform such exercise on consecutive days could lessen injury recovery times.…”
Section: Practicing the Strength Testmentioning
confidence: 99%
“…Grip strength correlates with mortality [ 90 92 ] and ability to perform activities of daily living [ 93 96 ]. Moreover, one review concluded that isometric hand grip exercise, which is often minimal in its prescription, reduces resting systolic blood pressure and induces hypoalgesia [ 97 ]. Also, the ability to perform such exercise on consecutive days could lessen injury recovery times.…”
Section: Practicing the Strength Testmentioning
confidence: 99%
“…Seniors can again benefit, as RT can contribute to improved cognitive function and memory performance. Apparently healthy individuals and individuals with psychological symptoms can experience increased feelings of well-being, self-efficacy, and reductions in schizophrenia, anxiety, depression, and other mood disorders with RT [ 10 , 11 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the highly cited benefits of RT for muscle strength, hypertrophy, and endurance [3][4][5][6][7], the health benefits of RT are now well established. RT has been positively associated with reducing cardiovascular risk factors such as reductions in blood lipids (i.e., total cholesterol, low-density lipoprotein cholesterol concentrations, and triglycerides), blood pressure, obesity, and glucose intolerance [8][9][10][11][12]. These RTinduced responses result in fewer reported incidences of diabetes, stroke, cancer, dementia, arthritis, coronary artery disease, and pulmonary disorders [8-10, 13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…To our best knowledge, one review study has summarized the association between IHE and health-related outcomes, which included cognition as an outcome ( Yamada et al, 2022 ). However, the conclusion on the effects of IHE on cognitive function was rather preliminary; the majority of included studies focused on the simultaneous episodic memory when performing IHE contractions, and only one pilot study investigated the training effect of IHE on cognitive function in that review.…”
Section: Introductionmentioning
confidence: 99%